Cost Analysis of the Plantation of Chayote for Farmers in Khao Kho District, Phetchabun Province. - Wongsurasate, Sawitree (Journal for Developing the Social and Community, 2021)
This research the objective is to study the general condition of Chayote for farmer’s plantation. And to analyze the cost of cultivating Chayote for farmers. By collecting data from using questionnaires and interviewing the group of farmers Chayote in Khao Kho District, Phetchabun Province, total of 37 people. From the collection of relevant research books. By using the data obtained to analyze by using mean and percentage. It was found that most of farmer’s plantation the Chayote for had planted Chayote for more than 2 years. The problems and obstacles encountered are diseases and insects. And need support from the government in finding sources of knowledge and techniques about planting Chayote. In terms of the cost of planting Chayote, it consists of raw materials, labor costs and production costs. Which has the following details Average raw material for planting per rai is equal to 14,187 baht. Average labor cost per rai with a value of 88,256 baht. And the cost of production that is used to plantation Chayote averaged per rai 82,836.82 baht. Which is included in the average cost of planting Chayote per rai. The total amount is 186,037.49 baht. As for the income from the sale of Chayote products in one year, the average per rai with a total income of 396,000 baht. In terms of gross profit, the total amount is 209,962.51 baht. Gross profit from sales is 30.46 %, while the cost of planting is 46.98 %. Which consists of raw materials 7.63 %, labor cost 47.85 % and production cost 44.52 %.